IMPLEMENTASI ALAT PERAGA OPERASI BILANGAN BULAT BAGI GURU SEKOLAH DASAR (SD) SE-KECAMATAN ILIR BARAT I PALEMBANG - Ratu Ilma (Universitas Sriwijaya, 2011)
The purpose of this activity is to increase the ability of teachers in 1) make mathematics manipulative Â as a media of operations of Â integer, 2) used mathematics manipulative is made in classroom simulation. Method of the activities performed is a demonstration, presentations and discussion. The participants of this activity are 25 teachers of â€œKecamatan Ilir Barat I